2021
DOI: 10.1155/2021/8772688
|View full text |Cite
|
Sign up to set email alerts
|

Refined Path Planning for Emergency Rescue Vehicles on Congested Urban Arterial Roads via Reinforcement Learning Approach

Abstract: Fast road emergency response can minimize the losses caused by traffic accidents. However, emergency rescue on urban arterial roads is faced with the high probability of congestion caused by accidents, which makes the planning of rescue path complicated. This paper proposes a refined path planning method for emergency rescue vehicles on congested urban arterial roads during traffic accidents. Firstly, a rescue path planning environment for emergency vehicles on congested urban arterial roads based on the Marko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Dilated causal convolution is used to solve the problem of the time dimension of big data. Among them, the expansion coefficient of the convolution kernel can be arbitrarily combined from the range of [1,2,4,8,16,32]. Through comparative experiments, it is found that the experimental results obtained by [1,2,4], [1,2,4,8,16], and [8,16,32] are relatively stable.…”
Section: Prediction Modulementioning
confidence: 99%
See 1 more Smart Citation
“…Dilated causal convolution is used to solve the problem of the time dimension of big data. Among them, the expansion coefficient of the convolution kernel can be arbitrarily combined from the range of [1,2,4,8,16,32]. Through comparative experiments, it is found that the experimental results obtained by [1,2,4], [1,2,4,8,16], and [8,16,32] are relatively stable.…”
Section: Prediction Modulementioning
confidence: 99%
“…As shown in Figure 1(b), in the top 10 toll-gates ranked by congestion in China, the vehicle speed may drop to 10 km/h and the congestion index may even be up to 50-60. It might additionally cause traffic accidents, energy consumption, and environmental pollution in the areas of these toll-gates [4]. In order to alleviate or avoid the occurrence of these problems, an increasing number of researchers are working on two aspects: traffic prediction and congestion evaluation of the toll-gates area, in which further studies on quantitively predicted traffic indicators might be an alternative way to solve the problem to evaluate the congestion.…”
Section: Introductionmentioning
confidence: 99%
“…For finding optimal solutions in complex urban environments, Koh et al propose a new deep reinforcement learning-based vehicle route optimization method for finding the best route for vehicles to reach their destinations and avoid congestion in complex urban traffic networks [35]. For a similar problem mentioned above, Yan et al develop a refined rescue route planning environment based on the Markov decision process for congested urban arterial roads [36]. A value-based deep reinforcement learning algorithm is used to plan EVs' routes in this environment, aiming to reach the accident scene in the shortest time and reduce the length of road vehicle queues in the road network.…”
Section: Machine-learning-based Algorithmsmentioning
confidence: 99%
“…Constantinescu and Patrascu aim to find the route with the least road occupancy to shorten the EV response time [29]. Yan et al provide optimal path planning for EVs to reach the scene of traffic accidents with the shortest time and the least length of road queuing [36]. Yang et al propose optimization objectives for path reliability and emergency response time [38].…”
Section: Objective Metricmentioning
confidence: 99%
“…The work of many authors has covered the answer to the first query. In work put forward by [8]- [10], the authors have tried to determine the attribute that should be measured to assess the performance of EMS.…”
Section: Litertaure Reviewmentioning
confidence: 99%